ORGANIZATION OF PRODUCTION OF INCREASE IN ENTERPRISE EFFICIENCY - N.I. KURGANSKAY (Advanced Engineering Research)
Organization of production is one of the directions of STP (Scientific Technological Progress). It place an important role in increase in enterprise efficiency. The application of new technologies is not always effective at the low level of organization. The increase in enterprise efficiency depends on organization of manufacturing processes.It can be achieved by the effective application of modern equipment, rational use of materials, energy, tools and labour resources. The purpose of developing organization of production is the improvement of economical results. That is why, determining the level of organization it is necessary to appreciate its in flounce on on economic indices.